Community Participation in the Development of Mekar Sari Village, Kumpeh District, Muaro Jambi Regency - Wulandari, Novi Wulandari; Mustika, Mustika; Suryani, Ade Irma (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
This study aims to determine the extent of community participation in the development of Mekar Sari Village, Kumpeh District, Muaro Jambi Regency. Village development is not solely the responsibility of the government but also requires the active involvement of the local community. Using a qualitative descriptive approach, this study describes the stages of community participation, from problem identification and formulation, data collection, analysis, to drawing conclusions and formulating recommendations. The results indicate that community participation is still partial and uneven across all development sectors. Inhibiting factors identified include a lack of outreach, limited information, and the dominance of certain actors in decision-making. However, there are positive initiatives undertaken by Village-Owned Enterprises (BUMDes) and community groups that serve as a starting point for strengthening public participation. The conclusions of this study emphasize the importance of transparency, two-way communication, and empowerment of villagers to promote inclusive and sustainable development.